2007
DOI: 10.1038/sj.onc.1210786
|View full text |Cite
|
Sign up to set email alerts
|

U19/Eaf2 knockout causes lung adenocarcinoma, B-cell lymphoma, hepatocellular carcinoma and prostatic intraepithelial neoplasia

Abstract: (Eaf2) is a potential human tumor suppressor that exhibits frequent allelic loss and downregulation in high-grade prostate cancer. U19/Eaf2, along with its homolog Eaf1, has been reported to regulate transcriptional elongation via interaction with the eleven-nineteen lysine-rich leukemia (ELL) family of proteins. To further explore the tumor-suppressive effects of U19/Eaf2, we constructed and characterized a murine U19/Eaf2-knockout model. Homozygous or heterozygous deletion of U19/Eaf2 resulted in high rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
112
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(121 citation statements)
references
References 23 publications
6
112
0
3
Order By: Relevance
“…However, intercrosses of EAF2/U19 heterozygous knock-out mice yielded Eaf2/U19-null offspring at Mendelian ratios at birth, suggesting that early mouse development did not require EAF2/U19 (10). Eaf2/U19 knockdown in zebrafish embryos alone caused defects in convergence and extension movements in our study.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, intercrosses of EAF2/U19 heterozygous knock-out mice yielded Eaf2/U19-null offspring at Mendelian ratios at birth, suggesting that early mouse development did not require EAF2/U19 (10). Eaf2/U19 knockdown in zebrafish embryos alone caused defects in convergence and extension movements in our study.…”
Section: Discussionmentioning
confidence: 68%
“…To investigate the function EAF2/U19 in vivo, we constructed a murine knock-out model. The EAF2/U19 knock-out mice develop B-cell lymphoma, lung adenocarcinoma, hepatocellular carcinoma, and prostate intraepithelial neoplasia with high frequency (10). In addition, we demonstrated that EAF2/U19 could bind to and stabilize the classic tumor suppressor-pVHL (11).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, our studies provided evidence that ELL alone has transactivation capability (32). In vitro and in vivo studies revealed U19/Eaf2 as a potential tumor suppressor (31,35), further supporting a role for ELL in tumor progression.…”
mentioning
confidence: 65%
“…The EAF2 locus exhibits frequent allelic loss in ϳ80% of advanced clinical prostate cancer specimens, and evidence for homozygous deletion also exists (1). EAF2 deficiency in mice leads to carcinogenesis in multiple tissues (2) as well as aspermatogenesis and reduced survival (3). In addition to EAF2, mammals also express EAF1, a protein that shares 58% identity and 74% similarity with EAF2.…”
mentioning
confidence: 99%